Agronomic, pollen and molecular aspects of Avena strigosa and Avena brevis and their respective hybrids = Aspectos agronômicos, polínicos e moleculares de Avena strigosa e Avena brevis e respectivos híbridos - Machado, Bianca Oliveira (2024)
Recognized as one of the main winter cereals, oats are cultivated worldwide and are one of the main winter crops in southern Brazil. The genus Avena is represented by several species, including wild and cultivated species, with different ploidy levels: diploids, tetraploids and hexaploids. The diploid species Avena strigosa Schreb. is widely used as an annual winter forage for grazing and used in the no-tillage system as soil cover. Due to its importance, genetic improvement seeks to select superior genotypes, in addition to incorporating genetic variability into programs, which includes interest in wild relatives. Crosses between A. strigosa and A. brevis Roth. (both diploids) generate fertile offspring. However, little information is available about A. brevis and its use in interspecific hybridization with A. strigosa. Chapter I aims to infer the fertility of pollen grains in genotypes of A. strigosa and A. brevis, as well as in the genotypes resulting from the cross between these species in the F1 and F2 generations. Chapter II aims to evaluate the genotypic performance of oat cultivars and lines, grown in Rio Grande do Sul, from 2016/2017 to 2021/2022, using the mixed model methodology. Chapter III seeks to determine the genetic dissimilarity of populations originating from crosses between A. strigosa and A. brevis in the F3 generation.